Hubungan Pendapatan Ekonomi Keluarga dan Tingkat Pendidikan Ibu terhadap Kejadian Stunting - Sagita Darma Sari; Vika Tri Zelharsandy (Jurnal Kebidanan Harapan Ibu Pekalongan, 2022)
Stunting or short is a condition that describes the nutritional status of undernutrition that has a chronic nature during the growth and development of children from the beginning of life which is presented with a z-score of height for age less than minus two standard deviations based on growth standards according to the World Health Organization. Objective: to determine the relationship between family economic income and maternal education level on the incidence of stunting. This study uses an analytical study method with a cross sectional approach. The data instrument used in this study is a checklist sheet. The sampling technique used was purposive sampling technique. The number of samples in this study were 30 toddlers who met the criteria. Analysis of the data used in the form of univariate and bivariate. The results of this study indicate that of the 30 respondents who have been collected data, the results of the p value of 0.131 are the relationship between family economic income and the incidence of stunting. The relationship between maternal education and the incidence of stunting with a p value of 0.003 based on the results of the chi-square value. Conclusion: There is no significant relationship between family economic income and the incidence of stunting, and there is a significant relationship between maternal education and the incidence of stunting.